Hierarchical Culture's Role as Moderator Between Job Engagement and Job Satisfaction ASN - Maeshade, Sheila; Etikariena , Arum; Hukama, Vizra (Universitas Islam Indonesia, 2025)
The decline in the number of Civil Servants (Aparatur Sipil Negara/ASN) in Indonesia, as reported by the Central Bureau of Statistics (BPS) from 2020 to 2023, highlights significant challenges within the country’s bureaucratic system. Environmental instability driven by bureaucratic reform has been linked to reduced employee engagement, as individuals struggle to adapt to ongoing changes. Such discomfort may impact employees’ job satisfaction an essential construct to examine, given the strategic role of ASN in delivering public services and executing governmental functions. While prior studies have established a positive relationship between work engagement and job satisfaction, limited research has examined the moderating role of organizational culture, particularly hierarchical culture, within this relationship. Guided by the Job Demands-Resources (JD-R) model (Bakker & Demerouti, 2008), this study investigates hierarchical culture as a contextual resource potentially moderating the relationship between work engagement and job satisfaction. Data were collected through validated self-report instruments, including the Job Satisfaction Survey(JSS), Utrecht Work Engagement Scale-9 (UWES-9), and the Organizational Culture Assessment Instrument. The survey was administered online to 203 ASN participants using convenience sampling. Hypothesis testing was conducted using PROCESS Macro Model 1 in SPSS v27.0 to examine the moderating effect. The results indicate that hierarchical culture does not significantly moderate the relationship between work engagement and job satisfaction. These findings suggest that hierarchical structures may not influence how engaged employees translate their engagement into satisfaction. Future research is encouraged to explore alternative moderators such as perceived organizational support or leadership styles to deepen understanding of the mechanisms underlying employee satisfaction in public sectorsettings.